REFLECTION OF FRUIT TREES UNDER THE INFLUENCE OF ENVIRONMENTAL STRESSES - Matilda Mema, Kejda Kristo, Emil Xhuvani (Chelonian Research Foundation, 2024)
Direct solar radiation affects the process and development of photosynthetic activity on fruit trees and on green plants in general. The influence of solar radiation on leaves can be analyzed using diffuse reflectance and also observing their color. The measurements were carried out with three types of leaves (sun, partial shade and shade) for Santa Maria (pear) variety in two areas under and above water. The reflectance values ​​provide the possibility to determine the parameters that evaluate the activity of the photosynthetic apparatus in two different areas in the same period. The resulting spectrum values allow the determination of brightness, "dominant" wavelength, and photochemical diffuse reflectance index (PRI).